Konsep Pewahyuan Al-Qur'an Menurut Stefan Wild - Moh Achwan Baharuddin (SUHUF, 2015)
The signifcance of the revelation or the Word of God has been the subject of the study for a long time, both for Muslims and non-Muslims scholars, especially when the revelation transformed from one thing to another, such as the Koran which was frst in the form of Kalamullah, to the form of pronunciation or memory and then becomes something which is written. The following brief article tries to present the revelation in the Orientalist perspective, Stefan Wild. Before going to the realm of revelation, the author tries to portray the Wild position among the works that have been done by other orientalists.